The impact of renewable energy on electricity accessibility and economic activity at the subnational level - Tiangco, Alab Jayme (School of Economics, University of the Philippines Diliman, 2019)
This thesis aims to determine whether or not having a power_generating plant in an area affects electrification, economic activity, and electricity prices. Electrification represents a certain measure of provincial development, and is defined by a percentage of households having access electricity in the given area. The study will cover the effect of a presence of an energy source in general. It will also differentiate between effects of renewable and non_renewable energy sources. In order to address these questions, the researchers will use Department of Energy_s power plant listing to locate the host municipalities. We then compare the electrification rates, energy prices, and nighttime light of these municipalities with other LGUs that do not have power plants. The researchers used DMSP_OLS Nighttime Lights Time Series dataset as an indicator of economic activity. This dataset maps the amount of light activity at night and its subsequent growth yearly. In theory, the more light there is in an area the more economic activity there is in that area (Henderson, Storeygard, and Weil, 2012, Mellander, Lobo, et. al, 2015). The unit of analysis of this study is municipality. A panel data for years 2011 to 2013 was constructed to run the analysis.